Nanotechnology for Targeted Therapy of Atherosclerosis - Hossaini Nasr, Seyedmehdi; Huang, Xuefei (Frontiers in Pharmacology, 2021)
Atherosclerosis is the major cause of heart attack and stroke that are the leading causes of death in the world. Nanomedicine is a powerful tool that can be engineered to target atherosclerotic plaques for therapeutic and diagnosis purposes. In this review, advances in designing nanoparticles with therapeutic effects on atherosclerotic plaques known as atheroprotective nanomedicine have been summarized to stimulate further development and future translation.